Betel quid chewing leads to the development of unique de novo malignancies in liver transplant recipients, a retrospective single center study in Taiwan. Issue 37 (September 2016) - Chen, Yi-Chan; Cheng, Chih-Hsien; Wang, Yu-Chao; Wu, Ting-Jun; Chou, Hong-Shiue; Chan, Kun-Ming; Lee, Wei-Chen; Lee, Chen-Fang; Soong, Ruey Shyang
Abstract : Abstract: Orthotopic liver transplantation (OLT) is the choice of treatment not only for end-stage liver disease and acute liver failure but also for hepatocellular carcinoma (HCC). The development of de novo malignancies after liver transplantation plays an important role in late mortality; the incidence of late mortality has increased owing to improved survival. The incidence of de novo malignancies is 2.3% to 25%, which is 2 to 3 times that of malignancies in the general population. The most commonly reported de novo malignancies in solid organs are skin cancer, Karposi sarcoma, and colon cancer according to the frequency of exposure to a specific carcinogen. We hypothesized that exposure to different carcinogens would change the distribution of de novo malignancies among patients after OLT. In Taiwan, 10% of the population is exposed to a unique carcinogen, the betel quid, which is associated with a high incidence of head and neck cancer (HNC) among the Taiwanese population. From 2004 to 2014, we retrospectively reviewed 484 cases post-OLT at our institution and 16 patients with 17 de novo malignancies were identified. Most of the patients had HNC, which is in contrast to previous literature reports. Univariate and multivariate analyses identified betel quid chewing as the main leading factor for HNC in the Taiwanese population. Routine screening of the oral mucosa in patients with the habit of betel quid chewing is recommended in Taiwan for the early detection of HNC. Routine screening with aggressive treatment after diagnosis of HNC in patients with the habit of chewing betel quid, who underwent OLT, resulted in good patient prognosis.